Modelling and estimation of health-related quality of life after hip fracture: A re-analysis of data from a prospective cohort study. Issue 1 (January 2018) - Parsons, N.; Griffin, X. L.; Achten, J.; Chesser, T. J.; Lamb, S. E.; Costa, M. L.
Abstract : Objectives: This study investigates the reporting of health-related quality of life (HRQoL) in patients following hip fracture. We compare the relative merits and make recommendations for the use for two methods of measuring HRQoL; (i) including patients who died during follow-up and (ii) including survivors only. Methods: The World Hip Trauma Evaluation has previously reported changes in HRQoL using EuroQol-5D for patients with hip fractures. We performed additional analysis to investigate the effect of including or excluding those patients who died during the first four months of the follow-up period. Results: The dataset included 503 patients, 25 of whom died between 30 days and four months of injury. There was a statistically significant difference in 30-day HRQoL between those alive (mean 0.331 and standard deviation (sd ) 0.360) and those dead (mean 0.156 andsd 0.421) by four months (independent-samples t -test; p 0.022). The estimated difference of 0.175 in HRQoL (95% confidence interval 0.025 to 0.325) was also highly clinically significant. Conclusion: When reporting HRQoL for patients after a hip fracture, excluding patients who die during follow-up leads to an overestimate of the effects of the intervention or treatment pathway. We would recommend that death-adjusted estimates should be used routinely when reporting HRQoL in this population. Cite this article : N. Parsons, X. L. Griffin, J. Achten, T. J. Chesser, S. E. Lamb, M. L. Costa. Modelling and estimation of health-related quality of life after hip fracture: A re-analysis of data from a prospective cohort study. Bone Joint Res 2018;7:1–5.